(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
The objective of the experiment was to evaluate the effects of recombinant bovine somatropin (rbST), and the reuse of the progesterone (P4) releasing devices in resynchronization, on the pregnancy rates of Nellore cows submitted to fixed-time artificial insemination. A group of 123 multiparae Nellore cows, was submitted to a resynchronization protocol: on day 0 a Bovine Intravaginal Device (DIB® ) with 1,0g of P4 was implanted, associated with intramuscular administration of 2,0mg of estradiol benzoate (IM); on day 8 DIB was removed; and 1,0mg of estradiol cypionate, 0,15mg of prostaglandin F2? and 300 UI of equine chorionic gonadotropin were administered; on day 10, fixed-time artificial insemination was conducted (FTAI). The cows were randomized into G1 (n=12) – without rbST / with used Bovine Intravaginal Device, G2 (n=50) – without rbST / with new DIB, G3 (n=11) - with rbST / with used DIB and G4 (n=50) – with rbST/ with new DIB. rbST was introduced on the eighth day of the protocol. Sixty days after TAI, pregnancy diagnoses were conducted, via rectal palpation. Blood samples were taken on day 0, 8 and 10 of the protocol, in order to assess P4 plasma concentrations. Pregnancy rates were statistically evaluated through Generalized Linear Models Theory and their significance was tested with Analysis of Deviance. Pregnancy rates were 58%, 40%, 81% and 48% for G1, G2, G3 and G4, respectively, with significant statistical difference for G3. Plasma concentrations of P4 were not statistically different among groups, or collections. In view of the results obtained, we concluded that the administration of rbST in association with P4 DIB, used for the third time, improves pregnancy rates. Estrus resynchronization and re-insemination positively impacted pregnancy rates.